2018
DOI: 10.1111/nph.15519
|View full text |Cite
|
Sign up to set email alerts
|

Boron: the essential element for vascular plants that never was

Abstract: Summary Although a requirement for boron is a well‐established feature of vascular plants, its designation, for almost a century, as essential is challenged and, instead, the proposal is made that it has never been so as conventionally defined. This is because an alternative interpretation of published evidence negates its compliance with one of the criteria for essentiality, that its effects are direct. The alternative, here postulated, is that boron is, and always has been, potentially toxic, a feature which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 39 publications
(49 reference statements)
0
56
0
Order By: Relevance
“…Recently, it has been also suggested that B is neither a beneficial nor an essential element for plant growth. Indeed, it was hypothesized that it is maintained in a homeostatic balance within the plant, thanks to the natural selection of constitutive biochemical mechanisms [41].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been also suggested that B is neither a beneficial nor an essential element for plant growth. Indeed, it was hypothesized that it is maintained in a homeostatic balance within the plant, thanks to the natural selection of constitutive biochemical mechanisms [41].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the various examples illustrating the essential role of B in plants, a recent paper by Lewis (2019) argued against the essentiality of B because, from the author's point of view, an alternative interpretation of published evidence negates its compliance with one of the criteria for essentiality: the direct metabolic effect. Lewis (2019) proposed that B is, and always has been, potentially toxic for plants, and this feature needs to be nullified for normal growth, development and reproduction.…”
Section: The Role Of Boron In Plantsmentioning
confidence: 99%
“…Previous studies indicated that the boron speciation within plant tissues observed in the current study likely consisted of unchanged boric acid, B complex binding with soluble phenypropanoids in the cytoplasm (B associated with carbonate) for detoxi cation of excess B, and B complex binding with insoluble carbohydrate polymers such as pectin on primary cell wall (tetrahedral B(OH) 4 ) and sucrose in phloem [46,47,41]. The predominant peak at 194 eV in sensitive accessions without added B may indicate the presence of free boric acid (trigonal B(OH) 3 ), which would lower pH in the cytoplasm.…”
Section: Discussionmentioning
confidence: 65%